Analisis Penerapan Manajemen Kinerja Model Deming (PDCA Cycle) Studi Kasus Pada Coffeshop Bestari Lampung Selatan - Ray Natanael Jericho Palawi; Muhammad Alwi Alhaqqi; Muhammad Reza Saputra; Aqbil Anshari Palawi (Fakultas Rekayasa dan Teknologi Industri, 2026)
The increasing business competition in the Coffeeshop industry requires every Coffeeshop to have a unique characteristic and always improve both operational and financial performance. This makes every business actor have a structured performance management system to increase competitiveness and business sustainability. Coffeeshop Bestari as one of the businesses in the culinary field faces challenges in improving individual employee performance and overall organizational performance in order to be able to achieve predetermined business targets. The research method used is a qualitative method with a descriptive approach. Data collection techniques are carried out through literature studies to strengthen the theoretical basis and semi-structured interviews with Coffeeshop Bestari management to obtain a real picture regarding the implementation of performance management and the PDCA Cycle (Plan, Do, Check, Act). The results show that Coffeeshop Bestari has a performance plan oriented towards increasing turnover and customer attraction. These efforts are carried out through increasing the number of employees and implementing a service strategy based on the 5S concept (smile, greet, greet, be polite, and courteous) as a standard of service to customers. The implementation of the PDCA Cycle helps management in conducting more systematic planning, directed implementation, periodic performance evaluation, and continuous improvement actions. This implementation provides a positive contribution to improving the quality of service, employee performance, and the effectiveness of achieving the objectives of Coffeeshop Bestari.